Cooperative stimulation of dendritic cells by Cryptococcus neoformans mannoproteins and CpG oligodeoxynucleotides. - Jennifer M Dan; Jennifer P Wang; Chrono K Lee; Stuart M Levitz (PLoS ONE)
While mannosylation targets antigens to mannose receptors on dendritic cells (DC), the resultant immune response is suboptimal. We hypothesized that the addition of toll-like receptor (TLR) ligands would enhance the DC response to mannosylated antigens. Cryptococcus neoformans mannoproteins (MP) synergized with CpG-containing oligodeoxynucleotides to stimulate enhanced production of proinflammatory cytokines and chemokines from murine conventional and plasmacytoid DC. Synergistic stimulation required the interaction of mannose residues on MP with the macrophage mannose receptor (MR), CD206. Moreover, synergy with MP was observed with other TLR ligands, including tripalmitoylated lipopeptide (Pam3CSK4), polyinosine-polycytidylic acid (pI:C), and imiquimod. Finally, CpG enhanced MP-specific MHC II-restricted CD4(+) T-cell responses by a mechanism dependent upon DC expression of CD206 and TLR9. These data suggest a rationale for vaccination strategies that combine mannosylated antigens with TLR ligands and imply that immune responses to naturally mannosylated antigens on pathogens may be greatly augmented if TLR and MR are cooperatively stimulated.